2014
DOI: 10.4314/jab.v76i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Date et densité optimales de semis du niébé [<i>Vigna unguiculata</i> (L.) Walp.] en association avec le mil [<i>Pennisetum glaucum</i> (L.) R. Br.]

Abstract: Date et densité optimales de semis du niébé en association avec le mil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
6
0
4
Order By: Relevance
“…The application rates of cow dung and horse manure were determined based on their nutrient content (N, P, and K) in conjunction with the nutritional requirements of the pearl millet plants, as outlined in previous studies ( Ouendeba and Teme, 2011 ; Mbaye et al., 2014 ) and summarized in Table 2 . Inorganic fertilizers were additionally applied to fulfill the N and K requirements of the crops, as specified in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The application rates of cow dung and horse manure were determined based on their nutrient content (N, P, and K) in conjunction with the nutritional requirements of the pearl millet plants, as outlined in previous studies ( Ouendeba and Teme, 2011 ; Mbaye et al., 2014 ) and summarized in Table 2 . Inorganic fertilizers were additionally applied to fulfill the N and K requirements of the crops, as specified in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The growth of two or more crops in combination often results in lower yields of both crops due to competition for limited essential resources 16 -18. Mbaye and al. 19 , working on different dates and seedling densities of cowpea associated with millet found no significant effect of cowpea on millet productivity and showed that the results differ by one year from other depending on dates and sowing densities.…”
Section: Effects Of Nitrogen Fertilization and Association With Cowpementioning
confidence: 96%
“…For cowpea, they were done from 25 to 30 July and 28 July to 3 August in 2019 and 2020, respectively. Cowpea sowings were shifted approximately 10 days later from those of sorghum in order to optimize its grain yield and biomass (Mbaye et al, 2014). Spacing was 80 cm between rows and 40 cm between plants within rows for all cultivars.…”
Section: Trial Establishment and Agronomic Management 2241 Mother Tri...mentioning
confidence: 99%
“…These comparative advantages can be explained by the beneficial relationships of complementarity between the two associated crops for the use of nitrogen resources, space (very different aerial architectures), and growth peaks (Justes et al, 2014;Barro et al, 2016;Louarn et al, 2016). Shifting the sowing date between the two associated crops reduces the interspecific competition (Mbaye et al (2014). Indeed, the symbiotic fixation of atmospheric nitrogen by cowpeas limits its competition with sorghum, which uses mineral nitrogen in the soil.…”
Section: Sorghum and Cowpea Intercrop Improves Grain And Fodder Bioma...mentioning
confidence: 99%
See 1 more Smart Citation